Existente versus persona: Luigi Pareyson y su apropiación crítica del existencialismo de Karl Jaspers. - Giménez Salinas, Constanza (Revista Estudios de Filosofía)
Pareyson raises a particular criticism of Jaspers' concept of existential shipwreck, understood as the annihilation of the existing due to its initude, preceded by a supreme moment of self-awareness and revelation. In contrast to the negativity and guilt that Jaspers assumes as inherent to initude and, paradoxically, as determinants of freedom, Pareyson interprets existence as a point of revelation of being in history. He does so by replacing the concept of implication between inite and ininite with that of incommensurability. Between an eternal non-relative absolute and a temporal relative inite. On this basis, he builds his concept of person as an "initiated initiative," that is, a freely chosen and operative agency, preceded by the establishment of an original relationship with the absolute.